2021
DOI: 10.3390/molecules26020444
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antimicrobial Stapled Peptides Based on Magainin 2 Sequence

Abstract: Magainin 2 (Mag2), which was isolated from the skin of the African clawed frog, is a representative antimicrobial peptide (AMP) that exerts antimicrobial activity via microbial membrane disruption. It has been reported that the helicity and amphipathicity of Mag2 play important roles in its antimicrobial activity. We investigated and recently reported that 17 amino acid residues of Mag2 are required for its antimicrobial activity, and accordingly developed antimicrobial foldamers containing α,α-disubstituted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 22 publications
0
36
0
Order By: Relevance
“…Stapling is a key technique of forcing peptides structure into an α-helical by the linkage of the side chains [ 335 ]. A very recent report from Demizu’s group designed and synthesized magainin 2 derivatives by stapling between the first and fifth position from the N-terminus, which showed a higher antimicrobial activity against both Gram-positive and Gram-negative bacteria than magainin 2, without exerting significant hemolytic activity [ 336 ].…”
Section: Rational Engineering Of Ampsmentioning
confidence: 99%
“…Stapling is a key technique of forcing peptides structure into an α-helical by the linkage of the side chains [ 335 ]. A very recent report from Demizu’s group designed and synthesized magainin 2 derivatives by stapling between the first and fifth position from the N-terminus, which showed a higher antimicrobial activity against both Gram-positive and Gram-negative bacteria than magainin 2, without exerting significant hemolytic activity [ 336 ].…”
Section: Rational Engineering Of Ampsmentioning
confidence: 99%
“…In a recent study, α-(4-pentenyl)-Ala was reported being used for modifying Magainin 2. The introduction of α-(4-pentenyl)-Ala in the i/i+ 4 position could stabilize its helical structure and improve the bioactivity [38]. In this study, although introducing the α-(4-Pentenyl)-Ala with a hydrocarbon side chain decreased the α-helical content, it also enhanced the antimicrobial activity and reduced the toxicity.…”
Section: Discussionmentioning
confidence: 66%
“…With this technique the peptides are fixed in an α-helical or β-sheet conformation; the secondary structure they are likely to attain upon insertion into the OM renders them less vulnerable to proteolytic degradation [ 35 , 54 , 55 , 56 ]. Various stapled peptides have been described as potent antimicrobial drugs, but few have been shown to act against bacteria in vivo and, to our knowledge, none have been described as acting in combination with other drugs [ 27 , 28 , 29 ]. Here, we describe the effect of hydrocarbon stapling on in vivo activity of two previously described linear antimicrobial peptides, L6 and L8 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latter is a technique that introduces an intramolecular side chain-to-side crosslink to increase α-helicity and thereby proteolytic stability [ 23 , 25 , 26 ]. Different stapled peptides have been described to show potential antimicrobial activity [ 27 , 28 , 29 ], however only a few have been shown to act against bacteria in vivo and, to our knowledge, stapled peptides have not been described as acting in synergy with antibiotics against bacterial infections in vivo [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%